Effect of nerapi Eruptions on Sand Mining Activities - Jazaul Ikhsan (National Cheng Kung University, 2014)
this study describes the sand mining activities in surrounding Mount Merapi, the Moun Merapi Eeruptions and why the sand mining activities are very active. the study method used in this research is study literature, interview and conducting questionnaire.